Energy harvesting from a floor structure based on multiple piezoelectric transducer beams. Issue 1 (18th June 2021) - Zhong, Xiang; Wang, Sheng; Chen, Jun; Liu, Xiangfu; Guan, Mingjie; Chen, Lin
Abstract: In this paper, an energy harvesting floor based on piezoelectric transducers is studied. A structure with multiple layers of piezoelectric beams is designed. Different striking frequencies are studied. Fourier transform is applied to analyze the frequency characteristic of the output voltage. Experiments are explored to find out the optimal external load resistance for maximum output power. The experimental results show that, with three piezoelectric transducers in a beam array, and a stroke of 4 mm at the striking frequency of 1.263 Hz, the maximum output power is 733.5 µW.